Implementasi Sistem Informasi Pengaduan Siswa Berbasis Web dengan Pemantauan Service Level Agreement - Zakhi Febriyan; Sri Surmalinda; Eko Purwanto (Bulletin of Computer Science Research, 2026)
A student complaint system serves as a school service channel allowing students to submit grievances, criticisms, and reports regarding activities and services within the school environment. Complaint management at SMK IPTEK Weru, Sukoharjo Regency, currently lacks digital system support; consequently, report logging is disorganized, resolution processes are time-consuming, and follow-up monitoring is suboptimal. This research aims to design and develop a web-based Student Complaint Information System to provide a more organized and integrated solution for complaint management. The system was built using the Waterfall approach, implemented in stages ranging from requirements identification, design, and application development to functional testing and system maintenance. Research data derived from direct observation, interviews, and literature reviews served as the foundation for system development. The system utilizes Laravel as the application framework and MySQL for data storage. Black-box testing was conducted to ensure that every function operates according to requirements. A key contribution of this research is the implementation of a Service Level Agreement (SLA) feature within the web-based system, enabling the school to monitor the timeliness of complaint resolution in a more structured manner. Results indicate that core features such as login, complaint submission, data management, status monitoring, and report generation function as designed. Meanwhile, User Acceptance Testing (UAT) yielded an acceptance score of 85.00%, placing it in the "Very Good" category. These results demonstrate that the developed system enhances the effectiveness of the complaint process, accelerates report handling, and facilitates complaint management for students, staff, and administrators at SMK IPTEK Weru, Sukoharjo Regency.